An Ironman triathlon reduces neuromuscular performance due to impaired force transmission and reduced leg stiffness - Mueller, S. M.; Knechtle, P.; Knechtle, B.; Toigo, M. (European Journal of Applied Physiology, 2015)
Purpose: An Ironman triathlon is associated with changes in body composition as well as decreases in neuromuscular function. While the changes in body composition occurring during an Ironman are well investigated, comprehensive data on the changes in neuromuscular performance are scarce. In the present study, we investigated the mechanical alterations underlying reported reductions in maximal muscular force and power after an Ironman race in men.